Anger is a gift - Oshiro, Mark (Tom Doherty Associates, 2018)
Six years ago, Moss Jefferies' father was murdered by an Oakland police officer. Along with losing a parent, the media's vilification of his father and lack of accountability has left Moss with near crippling panic attacks. Now, in his sophomore year of high school, Moss and his fellow classmates find themselves increasingly treated like criminals in their own school. New rules. Random locker searches. Constant intimidation and Oakland Police Department stationed in their halls. Despite their youth, the students decide to organize and push back against the administration. When tensions hit a fever pitch and tragedy strikes, Moss must face a difficult choice: give in to fear and hate or realize that anger can actually be a gift.